A composite anode plate for copper electrowinning and a preparation method thereof

By using composite anode plates in copper electrodistribution technology, the concentration polarization and anode corrosion problems caused by the increase in current density are solved, and the effects of reducing the tank voltage, extending service life and increasing the current density are achieved.

CN111101153BActive Publication Date: 2025-02-14KUNMING HENDERA SCI & TECH CO LTD +3
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010048065.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-01-16
Publication Date
2025-02-14
Estimated Expiration
2040-01-16

AI Technical Summary

Technical Problem

In the existing copper electrodistribution technology, the increase in current density leads to polarization of concentration, increase in tank voltage, coarse in cathode copper particles, accelerate the corrosion rate of the anode, and traditional anode materials have poor conductivity, easy bending deformation and easy contamination of cathode products. question.

Method used

A composite anode plate for copper electrostatic accumulation is adopted. The anode plate consists of a conductive beam, a fence-type anode plate bracket, a lead or lead alloy fixing frame and an insulating sheath. The first lead alloy layer is provided on the surface of the conductive beam, and the anode composite rod is made of a copper rod. Or consists of a copper alloy rod, a second lead alloy layer and a cobalt-rare earth/silicon carbide particle layer.

Benefits of technology

It significantly reduces the slot voltage, improves service life, enhances the current conduction efficiency, increases the current density by more than 3 times, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111101153B_ABST
    Figure CN111101153B_ABST
Patent Text Reader

Abstract

The present invention provides a composite anode plate for copper electrowinning, comprising a conductive beam, a fence-type anode plate bracket, a lead or lead alloy fixing frame, and an insulating sheath; a first lead alloy layer is provided on the surface of the conductive beam; the fence-type anode plate bracket is vertically connected to the conductive beam; the fence-type anode plate bracket is composed of a plurality of parallel anode composite rods; the lead or lead alloy fixing frame is vertically connected to the fence-type anode plate bracket; the insulating sheath is arranged in parallel on both sides of the fence-type anode plate bracket. The present application also provides a method for preparing the composite anode plate for copper electrowinning. The composite anode plate provided by the present invention is applied to copper electrowinning. Compared with the traditional Pb-0.06wt%Ca-1.2wt%Sn anode, the cell voltage can be reduced by 300mV, the service life can be extended by 2 times, the current conduction efficiency can be increased by more than 4%, and the current density can be increased to more than 3 times the original.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper electrowinning, and in particular to a composite anode plate for copper electrowinning and a preparation method thereof. Background Art

[0002] The full wet copper production requires a large amount of lead alloy anodes. At present, the current density is generally 200-260A / m 2 In the range of 10,000 tons of copper, the electrolysis cycle is 7 to 10 days. 3,000 to 4,000 anode plates are required for the production of 10,000 tons of copper. At the same time, a large number of electrolytic cells and stainless steel cathode plates are also required. The one-time investment is large and the recovery cycle is long. Under the existing conditions, increasing the current density is one of the effective ways to increase the output of electrolytic copper. However, the increase in current density will cause concentration polarization, increase the cell voltage, and cause the cathode copper particles to become coarser, the anode corrosion rate to accelerate, and the lead ion content in the solution to increase. Therefore, when increasing the current density, it is necessary to increase the electrolyte circulation speed, appropriately adjust the additives, and change the anode plate structure.

[0003] At present, the lead alloy anode used in industry can form an oxide film protective layer during the electrolysis process and has a relatively high safety guarantee in production, but the corrosion of the oxide layer on the surface of the anode will produce harmful substances in the electrolytic cell and pollute the cathode. In addition, the lead alloy anode needs an additional potential of 600mV to combine with oxygen to form a lead oxide layer on its surface during the electrolysis process, which will consume 30% of the electricity of each electrolytic cell. In order to solve the environmental problems and energy consumption problems caused by electrolytic copper, higher performance anode substitutes have been developed. For example:

[0004] 1) Lead-based Pb-Co alloy anode and lead-based Pb-Co3O4 composite anode are based on lead or lead alloy, and composite electrodeposited Pb-Co or Pb-Co3O4 alloy layer on its surface; Co3O4 is widely used in the field of electrochemistry and has excellent electrocatalytic activity. The experimental results show that Co 3+ Co3O4 and Co have excellent electrocatalytic activity in the copper electrowinning process; industrial tests show that the anode made of Pb alloy as the matrix and the composite deposition of Pb-Co3O4 composite alloy layer on its surface has a cell voltage of about 70mV lower than that of the traditional Pb-Ca-Sn alloy anode in the copper electrowinning process, and the energy consumption is reduced by about 4%. The doping of Co3O4 and Co can not only reduce the oxygen evolution overpotential, but also increase the corrosion resistance of the anode; however, the poor conductivity of the lead alloy matrix itself, easy bending and deformation, and easy contamination of the cathode product are unavoidable.

[0005] 2) Setting up coated titanium anode: This type of anode is a titanium electrode coated with a layer of precious metal oxide (such as RuO2 or IrO2) on the surface. Its advantages are low energy consumption (10% to 17%), which can not only avoid the deposition of lead in the electrolytic cell and the contamination of the cathode product, but also does not need to add cobalt sulfate; but the main disadvantages of this anode are that its service life is too short and the material cost is too high.

[0006] 3) Anodes made of lightweight aluminum as the inner core and lead alloy as the outer layer through melting or electroplating: However, there are still some difficult problems to solve. First, the fluidity of the lead alloy liquid and the possible local holes in large-sized anode plates cannot be solved. Second, some grain boundary gaps will appear in the coating. The oxygen generated during electrolysis will pass through the grain boundary gaps in the coating to oxidize the aluminum matrix and form an aluminum oxide film with poor conductivity, which will deteriorate the anode performance.

[0007] 4) Fence-type anode plate for non-ferrous metal electrolysis: improves the flowability of the electrolyte, improves the effect and quality of electrolytic non-ferrous metal collection, and avoids the defect of the cathode plate touching the anode plate when lifting; uses cheap aluminum rods as the substrate, which significantly reduces the material cost, but still has the disadvantages of interface resistance, short life and high cell voltage.

[0008] Therefore, it is necessary to further develop an anode with high current efficiency, low energy consumption, long-term use under high current density and high cathode copper product quality (less lead). Summary of the invention

[0009] The technical problem solved by the present invention is to provide a composite anode plate for copper electrowinning with good electrocatalytic activity, low cell voltage, long service life, high service current density and high electrical efficiency.

[0010] In view of this, the present application provides a composite anode plate for copper electrowinning, comprising a conductive beam, a fence-type anode plate support, a lead or lead alloy fixing frame, and an insulating sheath;

[0011] The surface of the conductive beam is provided with a first lead alloy layer; the conductive beam is composed of a copper rod or a copper alloy rod;

[0012] The fence-type anode plate support is vertically connected to the conductive beam; the fence-type anode plate support is composed of a plurality of parallel anode composite rods; the anode composite rod is composed of a copper rod or a copper alloy rod, a second lead alloy layer arranged on the surface of the copper rod or the copper alloy rod, and a cobalt-rare earth / silicon carbide particle layer arranged on the surface of the second lead alloy layer;

[0013] The lead or lead alloy fixing frame is vertically connected to the fence-type anode plate support to fix the anode composite rod of the fence-type anode plate support;

[0014] The insulating sheath is arranged parallel to the edge side of the fence type anode plate support to fix the edge of the fence type anode plate support.

[0015] Preferably, the first lead alloy layer comprises a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead alloy layer which are sequentially stacked, the tin layer is close to the surface end of the copper rod or copper alloy rod; the thickness of the tin layer is 1-5 μm, and the thickness of the lead-tin-silver-indium rare earth alloy layer is 10-50 μm; the second lead alloy layer comprises a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead-zirconium alloy layer which are sequentially stacked, the tin layer is close to the surface end of the copper rod or copper alloy rod; the thickness of the tin layer is 1-5 μm, and the thickness of the lead-tin-silver-indium rare earth alloy layer is 10-50 μm; the thickness of the first lead alloy layer is 12-30 mm, and the thickness of the second lead alloy layer is 3-24 mm.

[0016] Preferably, the lead zirconium alloy in the lead zirconium alloy layer is selected from one of lead calcium zirconium, lead calcium strontium zirconium, lead calcium tin zirconium, lead tin zirconium rare earth, lead calcium tin zirconium rare earth and lead silver tin zirconium rare earth, and the mass percentage of zirconium in the lead zirconium alloy is 0.01-0.5%.

[0017] Preferably, the content of tin in the lead-tin-silver-indium rare earth alloy layer is 8-18wt%, the content of silver is 0.01-0.3wt%, the content of indium is 0.05-0.2wt%, and the content of rare earth is 0.005-0.1wt%.

[0018] Preferably, the shape of the silicon carbide particles in the cobalt-rare earth / silicon carbide particle layer is rhombus or spherical, the particle size of the silicon carbide particles is 20 to 500 μm, and the proportion of the silicon carbide particles on the anode plate is 10 to 50 g / m 2 The particle size of the rare earth is 10 to 100 nm, and its proportion on the anode plate is 5 to 30 g / m 2 .

[0019] Preferably, the cross-section of the copper rod or copper alloy rod is an isomorphic circular shape, an isomorphic cross shape, an isomorphic rectangular shape or a rectangular rectangular shape; holes are provided on the surface of the copper rod, and the shapes of the holes are elliptical, circular, square and isomorphic, the major diameter of the holes is 1 to 4 mm, and the center distance between the two holes is 10 to 30 mm.

[0020] Preferably, the material of the insulating sheath is modified PE, modified PP, modified PE-PP, modified PVC-PP or modified PP-ABS; the material of the lead alloy fixing frame is selected from one of lead calcium silver, lead calcium silver strontium rare earth, lead calcium tin rare earth, lead calcium silver tin rare earth and lead calcium silver tin strontium rare earth.

[0021] The present application also provides a method for preparing the composite anode plate for copper electrowinning, comprising the following steps:

[0022] A) cleaning and activating the copper rod or copper alloy rod in sequence, and coating the surface of the activated copper rod or copper alloy rod with a first lead alloy layer;

[0023] The copper rod or copper alloy rod is sequentially cleaned and activated, a second lead alloy layer is coated on the surface of the activated copper rod or copper alloy rod, and an active cobalt-rare earth / silicon carbide composite particle layer is sprayed on the surface of the second lead alloy layer to obtain an anode composite rod;

[0024] B) assembling a plurality of anode composite rods into a fence type to obtain a fence type anode plate support;

[0025] The anode composite rods of the fence-type anode plate support are fixed by lead or lead alloy, and the edge side of the fence-type anode plate support is fixed by an insulating sheath;

[0026] C) connecting the conductive beam obtained in step A) with the integral fence-type anode plate support obtained in step B) to obtain a composite anode plate for copper electrodeposition.

[0027] Preferably, in step A), the preparation process of the first lead alloy layer is specifically as follows:

[0028] Placing the activated copper rod or copper alloy rod in a tinning solution for electroplating and cleaning; the tinning solution comprises: 20-50 g / L stannous sulfate, 150-300 g / L sulfuric acid, 0.05-2 g / L polyethylene glycol, and 1-5 ml / L surfactant;

[0029] The cleaned copper rod or copper alloy rod is dried and then placed in a molten lead-tin-silver-indium rare earth alloy liquid for hot dip plating, and finally the obtained copper rod or copper alloy rod is placed in a die-casting mold, poured with lead alloy liquid and die-casted;

[0030] In step A), the preparation of the second lead alloy layer is specifically as follows:

[0031] Placing the activated copper rod or copper alloy rod in a tin plating solution for chemical plating, wherein the chemical plating tin plating solution comprises: 10-50 g / L stannous chloride, 80-120 g / L trisodium citrate, 10-30 g / L sodium acetate, 60-120 g / L thiourea, 60-120 g / L sodium hypophosphite, and 0.1-0.5 g / L ascorbic acid;

[0032] Placing the chemically plated copper rod or copper alloy rod in a molten lead-tin-silver-indium rare earth solution for hot-dip plating;

[0033] The hot-dip-plated copper rod or copper alloy rod is placed in a drawing and extrusion machine to coat the molten lead alloy by drawing and extrusion, and then cooled;

[0034] The temperature of the drawing and extrusion is 80-300° C., and the speed is 1-16 m / min.

[0035] Preferably, the cobalt-rare earth / silicon carbide composite particles in the cobalt-rare earth / silicon carbide composite particle layer are prepared by ultrasonic chemical plating, specifically:

[0036] The silicon carbide particles are ultrasonically dispersed in a mixed solution of ammonium fluoride and hydrochloric acid, and then washed with water; then sensitized in a mixed solution of tin chloride dihydrate and concentrated hydrochloric acid, and then washed with water; then activated in a mixed solution of silver nitrate, glucose and ammonia water, and then washed with water;

[0037] The ratio of the silicon carbide particles to the hydrochloric acid is 1 g: (5-20) ml, and the amount of the ammonium fluoride in the mixed solution of the ammonium fluoride and the hydrochloric acid is 5-15 g / L;

[0038] The ratio of the silicon carbide particles to the concentrated hydrochloric acid is 1 g: (10-30) ml, and the amount of the tin chloride dihydrate in the mixed solution of the tin chloride dihydrate and the concentrated hydrochloric acid is 3-15 g / L;

[0039] The ratio of the silicon carbide particles to the ammonia water is 1 g: (5-20) ml, the amount of the silver nitrate in the mixed solution of silver nitrate, glucose and ammonia water is 1-5 g / L, and the amount of the glucose is 5-10 g / L;

[0040] The activated silicon carbide particles are subjected to chemical plating, wherein the formula of the chemical plating is: 20-40 g / L of cobalt sulfate, 40-80 g / L of trisodium citrate, 3-10 g / L of boric acid, 30-60 g / L of sodium hypophosphite, 5-20 g / L of nano rare earth, 0.1-0.5 g / L of nonionic surfactant, pH 8-10, washed with deionized water and then dried to obtain active cobalt-rare earth / silicon carbide composite particles.

[0041] The present application provides a composite anode plate for copper electrowinning, which comprises a conductive beam, a fence-type anode plate support, a lead or lead alloy fixing frame and an insulating sheath; wherein a first lead alloy layer is arranged on the surface of the conductive beam, and the fence-type anode plate support is composed of a plurality of parallel anode composite rods, wherein the anode composite rod is composed of a copper rod or a copper alloy rod, a second lead alloy layer arranged on the surface of the copper rod or the copper alloy rod, and a cobalt-rare earth / silicon carbide particle layer arranged on the surface of the second lead alloy layer; the arrangement of the conductive beam and the fence-type anode plate support forms an integral anode plate structure, which greatly reduces the resistance of the anode plate, improves the conduction efficiency of the anode plate, significantly reduces the cell voltage, and rapidly increases the current efficiency; the cobalt-rare earth / silicon carbide particle layer arranged on the surface of the anode composite rod of the fence-type anode plate support greatly improves the surface activity of the anode plate, accelerates the surface oxygen evolution rate, reduces the cell voltage, and does not need to add cobalt ions to the electrolytic copper solution during the use of copper electrowinning, and the current density of the anode plate can be increased by 3 times.

[0042] Furthermore, the provision of a tin layer, a lead-tin-silver-indium rare earth layer and a lead-zirconium alloy layer in the second alloy layer of the anode composite rod improves the bonding strength and hardness of the anode composite rod, and the introduction of zirconium element in the lead-zirconium alloy layer significantly improves the corrosion resistance and hardness of the lead-zirconium alloy layer, thereby extending the service life of the anode plate; the provision of a tin layer in the first alloy layer and the second alloy layer improves the coverage of the plating on the irregular copper surface, avoids the easy oxidation of the copper matrix during subsequent hot-dip plating of lead alloy, and makes it easy for copper and tin to generate η phase (Cu6Sn5), thereby achieving the purpose of metallurgical bonding.

[0043] Experimental results show that, when the composite anode plate described in the present application is used in copper electroplating, compared with the traditional Pb-0.06wt%Ca-1.2wt%Sn anode, the cell voltage can be reduced by 300mV, the service life is extended by 2 times, the current conduction efficiency is increased by more than 4%, and the current density can be increased to more than 3 times the original. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a schematic structural diagram of the composite anode plate for copper electrowinning of the present invention;

[0045] Figure 2 for Figure 1 AA cross-sectional diagram of the composite anode plate;

[0046] Figure 3 for Figure 1 BB cross-section diagram of the composite anode plate;

[0047] Figure 4 for Figure 1 Cross-sectional view of the medium copper rod lead alloy / active cobalt-rare earth / silicon carbide composite rod;

[0048] Figure 5Schematic diagram of the structure of drilling holes on the surface of the copper rod in the composite anode plate. DETAILED DESCRIPTION

[0049] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0050] In view of the series of problems existing in the composite anode plate for copper electrowinning in the prior art, the present application provides a composite anode plate for copper electrowinning. Due to the arrangement of the conductive beam and the fence-type anode plate support, and the arrangement of the cobalt-rare earth / silicon carbide particle layer on the surface of each anode composite rod in the fence-type anode plate support, the composite anode plate for copper electrowinning has the problems of high electrocatalytic activity, low cell voltage, long service life, high current density in service, and high electrical efficiency. Specifically, the structural schematic diagram of the composite anode plate for copper electrowinning described in the present application is as follows Figure 1 As shown, 1 is a copper or copper alloy conductive beam, 2 is a first lead alloy layer, 3 is a fence-type anode plate bracket, 4 is a lead or lead alloy fixing frame, 5 is an insulating sheath, and 7 is an insulator. More specifically, an embodiment of the present invention discloses a composite anode plate for copper electrowinning, wherein the surface of the conductive beam is provided with a first lead alloy layer; the conductive beam is composed of a copper rod or a copper alloy rod;

[0051] The fence-type anode plate support is vertically connected to the conductive beam; the fence-type anode plate support is composed of a plurality of parallel anode composite rods; the anode composite rod is composed of a copper rod or a copper alloy rod, a second lead alloy layer arranged on the surface of the copper rod or the copper alloy rod, and a cobalt-rare earth / silicon carbide particle layer arranged on the surface of the second lead alloy layer;

[0052] The lead or lead alloy fixing frame is vertically connected to the fence-type anode plate support to fix the anode composite rod of the fence-type anode plate support;

[0053] The insulating sheath is arranged parallel to the edge side of the fence type anode plate support to fix the edge of the fence type anode plate support.

[0054] In the composite anode plate for copper electrowinning, the conductive beam is composed of a copper rod or a copper alloy rod; a first lead alloy layer is arranged on the surface of the conductive beam, and the first lead alloy layer includes a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead alloy layer arranged in sequence, and the tin layer is close to the surface end of the copper rod or the copper alloy rod; the tin layer, the lead-tin-silver-indium rare earth alloy layer and the lead alloy layer arranged on the surface of the conductive beam improve the metallurgical bonding with the conductive beam and improve the strength and hardness of the composite anode plate. The thickness of the tin layer is 1 to 5 μm, the thickness of the lead-tin-silver-indium rare earth alloy layer is 10 to 50 μm, and the thickness of the first lead alloy layer is 12 to 30 mm. The content of tin in the lead-tin-silver-indium rare earth alloy layer is 8 to 18 wt%, the content of silver is 0.01 to 0.3 wt%, the content of indium is 0.05 to 0.2 wt%, the content of rare earth is 0.005 to 0.1 wt%, and lead is the balance. The lead alloy in the lead alloy layer is a lead alloy well known to those skilled in the art, and is specifically selected from Pb, Pb-Ca, Pb-Sn, Pb-Sb, Pb-Ca-Sn, and Pb-Sn-Sb. Figure 3 shown.

[0055] The fence-type anode plate support is vertically connected to the conductive beam, that is, the fence-type anode plate support is connected to the conductive beam, and the conductive beam is perpendicular to each anode composite rod of the fence-type anode plate support. The fence-type anode plate support is composed of a number of parallel anode composite rods, each of which is composed of a copper rod or a copper alloy rod, a second lead alloy layer arranged on the surface of the copper rod or the copper alloy rod, and a cobalt-rare earth / silicon carbide particle layer arranged on the surface of the second lead alloy layer; the copper rod or copper alloy rod in the anode composite rod can be the same as or different from the copper rod or copper alloy rod of the conductive beam, and the present application does not impose any special restrictions on this; the second lead alloy layer includes a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead-zirconium alloy layer which are sequentially stacked, and the tin layer is close to the surface end of the copper rod or the copper alloy rod; the thickness of the tin layer is 1 to 5 μm, and the thickness of the lead-tin-silver-indium rare earth alloy layer is 1 to 5 μm. The lead-zirconium alloy layer has a thickness of 10 to 50 μm, and a thickness of 3 to 24 mm; the content of tin in the lead-tin-silver-indium rare earth alloy layer is 8 to 18 wt%, the content of silver is 0.01 to 0.3 wt%, the content of indium is 0.05 to 0.2 wt%, the content of rare earth is 0.005 to 0.1 wt%, and lead is the balance; the lead-zirconium alloy in the lead-zirconium alloy layer is selected from one of lead-calcium-zirconium, lead-calcium-strontium-zirconium, lead-calcium-tin-zirconium, lead-tin-zirconium rare earth, lead-calcium-tin-zirconium rare earth, and lead-silver-tin-zirconium rare earth, and the mass percentage of zirconium in the lead alloy is 0.01 to 0.5%; the above-mentioned lead-zirconium alloy is a lead-zirconium alloy numerically determined by a person skilled in the art, and this application does not impose any special restrictions on this. The introduction of zirconium element in the lead-zirconium alloy layer in the second lead alloy layer significantly improves the corrosion resistance and strength of the lead alloy, and prolongs the service life of the composite anode plate.

[0056] The surface of the second lead alloy layer is also provided with a cobalt-rare earth / silicon carbide particle layer, the cobalt-rare earth / silicon carbide particles in the layer are in the shape of a rhombus or a sphere, the particle size of the silicon carbide particles is 20 to 500 μm, and in a specific embodiment, the particle size of the silicon carbide particles is 100 to 300 μm, and the proportion of the silicon carbide particles on the anode plate is 10 to 50 g / m 2 The particle size of the rare earth is 10 to 100 nm. In a specific embodiment, the particle size of the rare earth is 30 to 60 nm, and the proportion on the anode plate is 5 to 30 g / m 2; If the silicon carbide particles are too fine, they are embedded too shallowly in the lead alloy layer, and the particles are easy to fall off; if the particles are too coarse, they are embedded too deeply in the lead alloy layer, the specific surface area of ​​the particles is small, the catalytic activity of the composite anode plate is weak, and it is not conducive to the precipitation of oxygen; if the nano rare earth particle size is too small, there are too many particles adsorbed on the surface of silicon carbide, which is not conducive to the deposition of cobalt; if the particle size is too large, there are too few particles adsorbed on the surface of silicon carbide, so that too much cobalt is deposited on the surface of silicon carbide. Due to the large brittleness of cobalt, the bond between silicon carbide and cobalt is not firm, easy to fall off, and no catalytic effect is achieved. In the cobalt-rare earth / silicon carbide particles, the weight percentage of silicon carbide is 40-60%, the weight percentage of cobalt is 20-40%, and the weight percentage of rare earth is 10-40%. If the silicon carbide content is too high, the activity is weakened, and if it is too little, the composite particles have poor binding force; if the cobalt content is too high, the binding force is poor, and if it is too little, the activity is weak; rare earth plays the role of refining cobalt crystals, too much cobalt content is small, and if it is too little, the binding force between particles is poor.

[0057] The specific structural diagram of the anode composite rod and the conductive beam is as follows Figure 2 As shown, 6 is a cobalt-rare earth / silicon carbide composite particle layer.

[0058] The specific shape design of the anode composite rod and the copper rod or copper alloy rod of the conductive beam can be as follows: Figure 4 , Figure 5 As shown, specifically, the cross section of the copper rod or copper alloy rod is a heterogeneous circular shape, a heterogeneous cross shape, a heterogeneous rectangular shape or a rectangular rectangular shape; holes are arranged on the surface of the copper rod, and the shape of the holes is elliptical, circular, square and heterogeneous, the long diameter of the holes is 1 to 4 mm, and the center distance between the two holes is 10 to 30 mm. The holes arranged on the surface of the copper rod are conducive to enhancing the bite force between the copper or copper alloy and the lead alloy layer, and increasing the conductive cross-sectional area of ​​the lead alloy layer, thereby increasing the conduction efficiency of the plate.

[0059] Each anode composite rod in the fence-type anode plate bracket is fixed by a reinforcing rib, i.e., a lead or lead alloy fixing frame. The lead or lead alloy fixing frame is vertically arranged to the anode composite rod to enhance the fixing stability; the lead alloy in the fixing frame can be specifically selected from one of lead calcium silver, lead calcium silver strontium rare earth, lead calcium tin rare earth, lead calcium silver tin rare earth and lead calcium silver tin strontium rare earth.

[0060] Insulating sheaths are arranged on the left and right sides of the fence-type anode plate bracket to fix the sides of the fence-type anode plate bracket; the insulating sheaths are insulating sheaths well known to those skilled in the art, and there is no special limitation on this in the present application. The insulating sheaths in the present application are selected from modified PE, modified PP, modified PE-PP, modified PVC-PP or modified PP-ABS.

[0061] The present application also provides a method for preparing the composite anode plate for copper electrowinning, comprising the following steps:

[0062] A) cleaning and activating the copper rod or copper alloy rod in sequence, and coating the surface of the activated copper rod or copper alloy rod with a first lead alloy layer to obtain a conductive beam;

[0063] The copper rod or copper alloy rod is sequentially cleaned and activated, a second lead alloy layer is coated on the surface of the activated copper rod or copper alloy rod, and a layer of active cobalt-rare earth / silicon carbide composite particle layer is sprayed on the surface of the second lead alloy layer to obtain an anode composite rod;

[0064] B) assembling a plurality of anode composite rods into a fence type to obtain a fence type anode plate support;

[0065] The anode composite rods of the fence-type anode plate support are fixed by lead or lead alloy, and the two sides of the fence-type anode plate support are fixed by insulating sheaths;

[0066] C) connecting the conductive beam to the integral fence-type anode plate support obtained in step B) to obtain a composite anode plate for copper electrodeposition.

[0067] In the process of preparing the composite anode plate, the copper rod or copper alloy rod is firstly cleaned and activated in sequence, and the cleaning and activation treatment are technical means well known to those skilled in the art, and this application does not impose any particular restrictions on this; in a specific embodiment, the cleaning is specifically:

[0068] The copper rod or copper alloy rod is placed in a 5-8wt% NaOH solution at 60-80°C for 30-60 minutes, and then washed with clean water.

[0069] The activation treatment is specifically:

[0070] The cleaned copper rod or copper alloy rod is placed in a 5-18wt% HNO3 solution at 40-80°C for activation for 1-2 minutes, and then washed with clean water.

[0071] After the activation treatment, the surface of the obtained copper rod or copper alloy rod is coated with a first lead alloy layer to obtain a conductive beam having a surface coated with the first lead alloy layer. In the present application, the first lead alloy layer includes a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead alloy layer arranged in sequence; the preparation of the first lead alloy layer is specifically as follows:

[0072] The activated copper rod or copper alloy rod is placed in a tinning solution, electroplated, and cleaned; the tinning solution comprises: 20-50 g / L of stannous sulfate, 150-300 g / L of sulfuric acid, 0.05-2 g / L of polyethylene glycol, and 1-5 ml / L of a surfactant (preferably OP emulsifier, glycerol, sodium dodecyl sulfate, etc.);

[0073] The cleaned copper rod or copper alloy rod is dried and then placed in a molten lead-tin-silver-indium rare earth alloy liquid for hot-dip plating, and finally the obtained copper rod or copper alloy rod is placed in a die-casting mold, poured with lead alloy liquid and die-casted to obtain a conductive beam with a first lead alloy layer coated on the surface;

[0074] In the above process, the current density of the electroplating is 0.5-3A / dm 2 The electroplating temperature is 15-38°C and the time is 8-30 minutes; the drying temperature is 120-200°C and the time is 5-20 minutes; the hot-dip plating temperature is 300-450°C and the time is 1-10 minutes. The electroplating, hot-dip plating and die-casting are all well-known technical means to those skilled in the art, and the specific implementation process will not be described in detail in this application.

[0075] The present application also carries out the preparation of the anode composite rod, specifically: first, the copper rod or copper alloy rod is sequentially cleaned and activated, then the surface of the activated copper rod or copper alloy rod is coated with a second lead alloy layer, and finally a cobalt-rare earth / silicon carbide composite particle layer is sprayed on the surface of the second lead alloy layer to obtain the anode composite rod. The above-mentioned cleaning and activation treatment can be carried out in accordance with the cleaning and activation treatment of the above-mentioned conductive beam, and this application will not repeat it. In the present application, the second lead alloy layer includes a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead-zirconium alloy layer which are sequentially stacked, and thus the preparation of the second lead alloy layer is specifically as follows:

[0076] Placing the activated copper rod or copper alloy rod in a tin plating solution for chemical plating, wherein the chemical plating tin plating solution comprises: 10-50 g / L stannous chloride, 80-120 g / L trisodium citrate, 10-30 g / L sodium acetate, 60-120 g / L thiourea, 60-120 g / L sodium hypophosphite, and 0.1-0.5 g / L ascorbic acid;

[0077] Placing the chemically plated copper rod or copper alloy rod in a molten lead-tin-silver-indium rare earth solution for hot-dip plating;

[0078] The hot-dip-plated copper rod or copper alloy rod is placed in a drawing and extrusion machine to be coated with molten lead alloy by drawing and extrusion, and then cooled.

[0079] The temperature of the chemical plating is 50-90°C, and the time is 30-60 min; the temperature of the hot dip plating is 300-450°C, and the time is 0.1-10 min; the speed of the drawing and extrusion is 1-16 m / min, and the temperature is 80-300°C. In a specific embodiment, the temperature of the drawing and extrusion is 100-200°C, and the speed is 2-8 m / min; the cooling temperature is below 10°C; the drawing speed will affect the degree of bonding between the second lead alloy layer and the substrate. A slower speed is conducive to a tight bond, but too slow will affect production efficiency; ice water cooling is used to make the lead alloy more refined and produce instantaneous hardening, thereby improving the bonding strength between the substrate and the lead alloy and the hardness of the lead alloy.

[0080] The above-mentioned chemical plating, hot-dip plating and drawing and extrusion are all technical means well known to those skilled in the art, and will not be specifically described here.

[0081] The surface of the copper rod is chemically tinned, and the obtained tin coating is more uniform, and the coverage of the coating on the irregular copper surface is improved, which avoids the easy oxidation of the copper matrix during the subsequent hot-dip lead alloy plating, so that the copper and tin have generated η phase (Cu6Sn5), thereby achieving the purpose of metallurgical bonding.

[0082] Adding a small amount of indium and rare earth to the lead-tin-silver-indium rare earth alloy liquid reduces the melting temperature of the lead alloy liquid, making the temperature difference between the tin plating and the lead alloy not much, so as to achieve the purpose of easily forming a gradient metallurgical bonding of copper / tin / lead-tin-silver-indium rare earth. In addition, a small amount of silver can improve the fluidity of the alloy liquid and the oxidation resistance and conductivity of the plating.

[0083] After the second lead alloy layer is prepared, an active cobalt-rare earth / silicon carbide composite particle layer is sprayed on the surface of the second lead alloy layer to obtain an anode composite rod; before spraying, it is preferably cleaned with acetic acid and hydrogen peroxide solution in a volume ratio of 3:1 and then washed with water before spraying, and the spraying is an explosion spraying method. Specifically:

[0084] The silicon carbide particles are ultrasonically dispersed in a mixed solution of ammonium fluoride and hydrochloric acid, washed with water, sensitized in a mixed solution of tin chloride dihydrate and concentrated hydrochloric acid, washed with water, activated in a mixed solution of silver nitrate, glucose and ammonia water, and finally washed with water;

[0085] The ratio of the silicon carbide particles to the hydrochloric acid is 1 g: (5-20) ml, and the amount of the ammonium fluoride in the mixed solution of the ammonium fluoride and the hydrochloric acid is 5-15 g / L;

[0086] The ratio of the silicon carbide particles to the concentrated hydrochloric acid is 1 g: (10-30) ml, and the amount of the tin chloride dihydrate in the mixed solution of the tin chloride dihydrate and the concentrated hydrochloric acid is 3-15 g / L;

[0087] The ratio of the silicon carbide particles to the ammonia water is 1g: (5-20)ml, the amount of the silver nitrate in the mixed solution of silver nitrate, glucose and ammonia water is 1-5g / L, and the amount of the glucose is 5-10g / L;

[0088] The activated silicon carbide particles are subjected to chemical plating, wherein the formula of the chemical plating is: 20-40 g / L of cobalt sulfate, 40-80 g / L of trisodium citrate, 3-10 g / L of boric acid, 30-60 g / L of sodium hypophosphite, 5-20 g / L of nano rare earth, 0.1-0.5 g / L of nonionic surfactant (including polyethylene glycol 6000, preferably polyvinyl pyrrolidone (PVP), polyoxyethylene ether (AEO), etc.), pH 8-10, washed with deionized water and then dried to obtain active cobalt-rare earth / silicon carbide composite particles.

[0089] In the above process of preparing cobalt-rare earth / silicon carbide composite particles, the coarsening and ultrasonic dispersion of the mixed solution of ammonium fluoride and hydrochloric acid, the activation of silver nitrate and the chemical plating of cobalt, rare earth and silicon carbide particles improve the binding force of Co and SiC, the coverage of Co, and further improve the service life of the composite anode plate. The content of NH4F has a great influence on the coarsening effect of silicon carbide particles. If the content is too low, the coarsening is not thorough, affecting sensitization, activation and incomplete chemical plating coating. If the content is too high, SiC is consumed too much, which is not conducive to activation and the integrity of chemical plating coating.

[0090] After the conductive beam and the anode composite rod are prepared, they are assembled according to the structure of the composite anode plate, specifically:

[0091] Assembling the composite anode plate into a fence type to obtain a fence type anode plate support;

[0092] The anode composite rods of the fence-type anode plate support are fixed by lead or lead alloy, and the two sides of the fence-type anode plate support are fixed by insulating sheaths;

[0093] The conductive beam is connected to the fence-type anode plate support to obtain a composite anode plate for copper electrowinning.

[0094] The long-life energy-saving fence-type composite anode plate provided by the present invention is applied to copper electrowinning. Compared with the traditional Pb-0.06wt%Ca-1.2wt%Sn anode, the cell voltage can be reduced by 300mV, the service life is extended by 2 times, the current conduction efficiency is increased by more than 4%, and the current density can be increased to more than 3 times the original.

[0095] In order to further understand the present invention, the composite anode plate for copper electrowinning and the preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments. The protection scope of the present invention is not limited by the following embodiments.

[0096] Example 1

[0097] like Figure 1 As shown, Figure 1 The present invention is a schematic structural diagram of a composite anode plate for copper electrowinning, which comprises a copper or copper alloy conductive beam (1), a first lead alloy layer (2) coated on the surface of the copper or copper alloy conductive beam (1), and a fence-type anode plate support (3) welded to the bottom of the copper or copper alloy conductive beam (1); the fence-type anode plate support is assembled from a plurality of anode composite rods, the reinforcing ribs between each anode composite rod constituting the fence-type anode plate support are fixed by lead and lead alloy (4), and the fence-type anode plate support is fixed on the left and right sides by an insulating sheath (5), and each anode composite rod is composed of a copper rod or a copper alloy rod, a second lead alloy layer arranged on the surface of the copper rod or the copper alloy rod, and a cobalt-rare earth / silicon carbide particle layer arranged on the surface of the second lead alloy layer (6);

[0098] The copper rod described in this embodiment has a cross-section of an isomorphic elliptical shape; the long axis of the elliptical copper rod is 100 mm, and the short axis is 8 mm; the copper rod surface is perforated, the shape of the hole is elliptical, the long diameter of the hole is 2 mm, and the center distance between the two holes is 10 mm; the thickness of the lead or lead alloy coated on the copper or copper alloy rod core is 6 mm;

[0099] The first lead alloy layer (2) has the following structures: a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead-calcium alloy layer coated on the surface of copper or copper alloy, the middle layer is a tin layer and a lead-tin-silver-rare earth layer, the thickness of the tin layer is 2 μm, the thickness of the lead-tin-silver-indium rare earth alloy layer is 20 μm; the thickness of the lead-calcium alloy layer (2) is 14 mm;

[0100] The insulating sheath material used is modified PE, modified PP, modified PE-PP, modified PVC-PP or modified PP-ABS;

[0101] The second lead alloy layer is composed of: a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead-zirconium alloy layer coated on the surface of copper or copper alloy, the middle layer is a tin and lead-tin-silver rare earth layer, the material of the lead-zirconium alloy layer is lead-calcium-tin-zirconium, and the mass percentage of zirconium in the lead alloy is 0.1%;

[0102] The reinforcing ribs between the composite anode rods are die-cast by a die-casting machine, and their components are lead, calcium, tin and rare earth;

[0103] The surface of the composite anode rod is sprayed with a layer of active cobalt-rare earth / silicon carbide composite particles by explosion spraying. The silicon carbide particles are rhombus or spherical in shape, with a particle size of 100 μm and a proportion of 20 g / m on the anode plate. 2 ; The rare earth particle size is 20nm, and the proportion on the anode plate is 10g / m 2 ;

[0104] In the intermediate layer of lead-tin-silver-indium rare earth alloy, the mass percentage of tin is 10%, the mass percentage of silver is 0.02%, the mass percentage of indium is 0.1%, and the mass percentage of rare earth is 0.05%.

[0105] The steps of the preparation method of the composite anode plate for copper electrowinning in this embodiment are as follows:

[0106] (1) Preparation of copper or copper alloy conductive beam coated with lead alloy layer: First, the copper beam is degreased and activated: in a 5-8% NaOH solution, the temperature is controlled at 60-80°C, degreased for 30-60 minutes, then immediately rinsed with water, and then immersed in a 5-18% HNO3 solution for activation for 1-2 minutes, the temperature is controlled at 40°C, and then rinsed with deionized water; then the treated copper is placed in a tinning solution at 1A / dm 2 Electroplating for 10 minutes at a current density, controlling the temperature at 15-38°C, the tin plating solution formula is: 25g / L stannous sulfate, 180g / L sulfuric acid, 0.1g / L polyethylene glycol 6000, 2ml / L glycerol, and then immediately washing with deionized water; then placing the treated copper in an oven at a controlled temperature of 150°C for drying for 10 minutes, immediately placing it in a molten lead-tin-silver-indium rare earth alloy liquid for hot dip plating at a temperature of 300°C for 1 minute to obtain a copper conductive beam coated with a lead-tin-silver-indium rare earth alloy; finally placing the treated copper conductive beam in a die-casting mold, pouring the lead alloy liquid, and performing die-casting to obtain a copper or copper alloy conductive beam coated with a lead alloy;

[0107] (2) Preparation of copper rod lead alloy / active cobalt-rare earth / silicon carbide composite anode rod: First, the copper rod is degreased and activated in a 5-8% NaOH solution at a controlled temperature of 60°C for 30-60 min, then immediately rinsed with water, and then immersed in a 5% HNO3 solution for activation for 1-2 min at a controlled temperature of 40°C-50°C, and then rinsed with deionized water;

[0108] (3) placing the copper rod substrate treated in step (2) in a chemical tin plating solution and soaking it for 30 minutes, controlling the temperature to 50° C., wherein the tin plating solution comprises: 20 g / L stannous chloride, 80 g / L trisodium citrate, 10 g / L sodium acetate, 60 g / L thiourea, 60 g / L sodium hypophosphite, pH 2, 0.1 g / L ascorbic acid, washing with deionized water and drying with hot air at 100 to 120° C.;

[0109] (4) placing the copper rod treated in step (3) in a molten lead-tin-silver-indium rare earth solution and plating it at a temperature of 300-450° C. for 2 min to obtain a copper rod lead-tin-silver-indium rare earth alloy;

[0110] (5) placing the copper rod lead-tin-silver-indium rare earth alloy obtained in step (4) in a drawing and extrusion machine at a speed of 8 m / min, controlling the drawing die temperature at 100° C., coating the molten lead-zirconium alloy on the surface of the copper rod lead-tin-silver-indium rare earth alloy by drawing and extrusion, then cooling the obtained copper rod lead alloy to 10° C. by an ice water freezer, and shearing it into a plurality of copper-based lead alloy rods of the same size as required;

[0111] (6) The copper-based lead alloy rod obtained in step (5) is cleaned with an acetic acid and hydrogen peroxide solution having a volume ratio of 3:1 and then washed with deionized water, and a layer of active cobalt-rare earth / silicon carbide composite particles is sprayed on its outer surface by explosion to obtain an anode composite rod;

[0112] (7) Preparation of fence-type composite anode plates: First, assemble the anode composite rods obtained in step (6), fix the composite rods constituting the fence-type anode plate support to each other with lead and lead alloy, and fix the left and right sides of the fence-type anode plate support with insulating sheaths, then weld the copper alloy conductive beam to the copper rod of the fence-type anode plate below, and then weld the lead alloy on the conductive beam to the lead alloy on the copper rod, and finally install insulators on the plate surface to obtain a fence-type composite anode plate.

[0113] The active cobalt-rare earth / silicon carbide composite particles are prepared by ultrasonic chemical plating, and the specific process is as follows: (1) coarsening, sensitization and activation: first, the silicon carbide particles are placed in a mixed solution of 10g / L NH4F+10ml HCl and ultrasonically dispersed at 40°C for 30 minutes, and then rinsed with deionized water. Then, they are sensitized in a mixed solution of 5g / L SnC12·2H2O+20ml / L concentrated hydrochloric acid at 25°C for 20 minutes, washed with hot water, and then activated in a mixed solution of 1g / L AgNO3+5g / L glucose+10ml ammonia water at 25°C for 30 minutes, and then washed with deionized water at 60°C; (2) the activated silicon carbide particles are immersed in a chemical composite plating solution, and a mechanical stirrer and ultrasonic stirring are used during the reaction process. The temperature is controlled at 50°C for 1 to 2 hours. The solution formula is: 20g / L cobalt sulfate, 40g / L trisodium citrate, 5g / L boric acid, 40g / L sodium hypophosphite, 10g / L nano rare earth, pH 8-10, non-ionic surfactant 0.1 g / L, washed with deionized water and dried at 110°C for 1-2 h to obtain active cobalt-rare earth / silicon carbide composite particles.

[0114] The fence-type composite anode plate for copper electrowinning prepared in this embodiment is electrolyzed in a copper electrolyte under the following conditions: electrolyte copper ion concentration is 50 g / L, sulfuric acid concentration is 180 g / L, electrolyte temperature is 40°C, iron ion is 1 g / L, Cl- ion is 20 mg / L, current density is 200 A / m 2Compared with the traditional Pb-0.06wt.%Ca-1.2wt.%Sn anode, the fence-type composite anode plate has a 4% higher electrical efficiency, a 240mV lower cell voltage, and a 1.5-fold longer life.

[0115] Example 2

[0116] The structure of the fence-type composite anode plate for copper electrowinning in this embodiment is the same as that in embodiment 1, except that: the cross section of the copper rod is a heterogeneous rectangular shape; its major axis is 100 mm, and its minor axis is 4 mm;

[0117] The first lead alloy layer coated on the surface of the copper or copper alloy conductive beam is sequentially: a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead alloy layer arranged on the surface of the base copper or copper alloy, the thickness of the tin layer is 2 μm, the thickness of the lead-tin-silver-indium rare earth alloy layer is 20 μm; the thickness of the first lead alloy layer is 18 mm; the lead alloy in the lead alloy layer is a lead-tin-antimony alloy;

[0118] The second lead alloy layer is sequentially: a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead-zirconium alloy layer arranged on the surface of the base copper or copper alloy, the thickness of the tin layer is 2 μm, the thickness of the lead-tin-silver-indium rare earth alloy layer is 20 μm; the thickness of the second lead alloy layer is 4 mm; the lead-zirconium alloy in the lead-zirconium alloy layer is lead-silver-tin-zirconium rare earth, wherein the mass percentage of zirconium in the lead alloy is 0.2%;

[0119] In the lead-tin-silver-indium rare earth alloy in the first lead alloy layer and the second lead alloy layer, the mass percentage of tin is 18%, the mass percentage of silver is 0.3%, the mass percentage of indium is 0.2%, and the mass percentage of rare earth is 0.05%;

[0120] The insulation sheath material used is modified PE;

[0121] The reinforcing ribs between the anode composite rods are die-cast by a die-casting machine, and the components thereof are lead, calcium, silver, tin, strontium and rare earth;

[0122] The surface of the composite anode rod is sprayed with a layer of active cobalt-rare earth / silicon carbide composite particles by explosion spraying. The silicon carbide particles are rhombus or spherical in shape, with a particle size of 100 μm and a proportion of 40 g / m on the anode plate. 2 ; The rare earth particle size is 50nm, and the proportion on the anode plate is 20g / m 2 .

[0123] The steps of preparing a long-life energy-saving fence-type composite anode plate for copper electrowinning are as follows:

[0124] (1) Preparation of copper or copper alloy conductive beam coated with lead alloy: First, the copper beam is degreased and activated. It is degreased in an 8% NaOH solution at a temperature of 70°C for 50 minutes, then immediately rinsed with water, and then immersed in a 15% HNO3 solution for activation for 2 minutes at a temperature of 60°C, and then rinsed with deionized water; then the treated copper is placed in a tinning solution at 1A / dm 2 Electroplating for 20 minutes at a current density and controlling the temperature at 25°C, wherein the tin plating solution formula is: 450 g / L stannous sulfate, 180 g / L sulfuric acid, 0.1 g / L polyethylene glycol 6000, and 2 ml / L OP emulsifier, and then immediately washing with deionized water; then placing the treated copper in an oven and controlling the temperature at 100°C for drying for 10 minutes, immediately placing it in a molten lead-tin-silver-indium rare earth alloy liquid and controlling the temperature at 350°C for hot dip plating for 5 minutes to obtain a copper conductive beam coated with a lead-tin-silver-indium rare earth alloy; finally, placing the treated copper conductive beam in a die-casting mold, pouring the lead alloy liquid, and performing die-casting to obtain a copper or copper alloy conductive beam coated with a lead alloy; the mass percentage of tin in the lead-tin-silver-indium rare earth alloy liquid is 18%, the mass percentage of silver is 0.3%, the mass percentage of indium is 0.2%, and the mass percentage of rare earth is 0.05%; the mass percentage of tin in the lead-tin-antimony alloy liquid is 0.6%, and the mass percentage of antimony is 0.6%;

[0125] (2) Preparation of anode composite rod: First, the copper rod was degreased and activated in a 6% NaOH solution at 70°C for 40 min, then immediately rinsed with water, and then immersed in 15% HNO3 for activation for 1 min at 40°C, and then rinsed with deionized water;

[0126] (3) placing the copper rod substrate treated in step (2) in a chemical tin plating solution and soaking it for 40 minutes, controlling the temperature to 70°C, wherein the formula of the tin plating solution is: 30 g / L stannous chloride, 100 g / L trisodium citrate, 20 g / L sodium acetate, 80 g / L thiourea, 100 g / L sodium hypophosphite, pH 1, 0.4 g / L ascorbic acid, washing with deionized water and drying with hot air at 120°C;

[0127] (4) Plating the copper rod treated in step (3) in a molten lead-tin-silver-indium rare earth solution at a controlled temperature of 35° C. for 1 min to obtain a copper rod having a surface coated with a lead-tin-silver-indium rare earth alloy layer; the mass percentage of tin in the lead-tin-silver-indium rare earth alloy solution is 18%, the mass percentage of silver is 0.3%, the mass percentage of indium is 0.2%, and the mass percentage of rare earth is 0.05%;

[0128] (5) placing the copper rod obtained in step (4) in a drawing and extrusion machine at a speed of 6 m / min, controlling the temperature of the drawing die at 180° C., coating the molten lead-silver-tin-zirconium rare earth alloy on the surface of the copper rod lead-tin-silver-indium rare earth alloy by drawing and extrusion, then cooling the obtained copper rod lead-silver-tin-zirconium rare earth alloy to 5° C. by an ice water freezer, and shearing it into a plurality of copper-based lead alloy rods of the same size as required; the mass fraction of silver in the lead-silver-tin-zirconium rare earth alloy is 0.15%, the mass fraction of tin is 1.2%, the mass fraction of zirconium is 0.2%, and the mass fraction of rare earth is 0.03%;

[0129] (6) The copper-based lead alloy rod obtained in step (5) is cleaned with an acetic acid and hydrogen peroxide solution in a volume ratio of 3:1 and then washed with deionized water, and a layer of active cobalt-rare earth / silicon carbide composite particles is sprayed on its outer surface by explosion spraying to obtain a copper rod lead alloy / active cobalt-rare earth / silicon carbide composite anode rod;

[0130] (7) Preparation of a fence-type composite anode plate: First, assemble the composite anode rods obtained in step (6), fix the composite rods constituting the fence-type anode plate support to each other using lead and lead alloy, and fix the left and right sides of the fence-type anode plate support with insulating sheaths, then weld the copper alloy conductive beam to the copper rod of the fence-type anode plate below, then weld the lead alloy layer on the conductive beam to the lead-zirconium alloy layer on the copper rod, and finally install an insulator on the plate surface to obtain a fence-type composite anode plate;

[0131] The above-mentioned active cobalt-rare earth / silicon carbide composite particles are prepared by ultrasonic chemical plating. The specific process is as follows: (1) coarsening, sensitization and activation: first, the silicon carbide particles are placed in a mixed solution of 10g / L NH4F+10ml HCl and ultrasonically dispersed at 40°C for 30 minutes, rinsed with deionized water, and then sensitized in a mixed solution of 5g / L SnC12·2H2O+20ml / L concentrated hydrochloric acid at 25°C for 20 minutes, washed with hot water, and then activated in a mixed solution of 1g / L AgNO3+5g / L glucose+10ml ammonia water at 25°C for 30 minutes, and washed with deionized water at 60°C; (2) the activated silicon carbide particles are immersed in a chemical composite plating solution, and a mechanical stirrer and ultrasonic stirring are used during the reaction process. The temperature is controlled at 80°C for 2 hours. The solution formula is: 30g / L cobalt sulfate, 60g / L trisodium citrate, 8g / L boric acid, 40g / L sodium hypophosphite, 15g / L nano rare earth, pH 8.9, polyethylene glycol 2000 0.2 g / L, washed with deionized water and dried at 110°C for 2 h to obtain active cobalt-rare earth / silicon carbide composite particles.

[0132] The fence-type composite anode plate for copper electrowinning prepared in this embodiment is electrolyzed in a copper electrolyte under the following conditions: electrolyte copper ion concentration is 50 g / L, sulfuric acid concentration is 180 g / L, electrolyte temperature is 40°C, iron ion is 1 g / L, Cl- ion is 20 mg / L, current density is 400 A / m 2 Compared with the traditional Pb-0.06wt.%Ca-1.2wt.%Sn anode, the fence-type composite anode plate has a 5% higher electrical efficiency, a 280mV lower cell voltage, and a 2-fold longer life.

[0133] Example 3

[0134] The structure of a fence-type composite anode plate for copper electrowinning in this embodiment is the same as that in embodiment 1, except that: the cross section of the copper rod in this embodiment is a heterogeneous circular shape; the diameter of the circular copper rod is 20 mm;

[0135] The first lead alloy layer coated on the surface of the copper or copper alloy conductive beam is sequentially: a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead alloy layer arranged on the surface of the base copper or copper alloy, the thickness of the tin layer is 1 μm, the thickness of the lead-tin-silver-indium rare earth alloy layer is 10 μm; the thickness of the first lead alloy layer is 12 mm; the lead alloy in the lead alloy layer is specifically a lead-calcium-tin alloy;

[0136] The second lead alloy layer is sequentially: a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead-zirconium alloy layer arranged on the surface of the base copper or copper alloy, the thickness of the tin layer is 1 μm, the thickness of the lead-tin-silver-indium rare earth alloy layer is 10 μm; the thickness of the second lead alloy layer is 6 mm; the lead-zirconium alloy in the lead-zirconium alloy layer is a lead-calcium-zirconium alloy, and the mass percentage of zirconium in the lead-zirconium alloy is 0.01%;

[0137] In the lead-tin-silver-indium rare earth alloy in the lead-tin-silver-indium rare earth alloy layer in the first lead alloy layer and the second lead alloy layer, the mass percentage of tin is 8%, the mass percentage of silver is 0.01%, the mass percentage of indium is 0.05%, and the mass percentage of rare earth is 0.005%;

[0138] The surface of the composite anode rod is sprayed with a layer of active cobalt-rare earth / silicon carbide composite particles by explosion spraying. The silicon carbide particles are rhombus or spherical in shape, with a particle size of 20 μm and a proportion of 50 g / m on the anode plate. 2 ; The rare earth particle size is 10nm, and the proportion on the anode plate is 30g / m 2 ;

[0139] The insulation sheath material used is modified PP;

[0140] The reinforcing ribs between the anode composite rods are die-cast by a die-casting machine, and the components thereof are lead, calcium and silver;

[0141] The steps of preparing a long-life energy-saving fence-type composite anode plate for copper electrowinning are as follows:

[0142] (1) Preparation of copper or copper alloy conductive beam coated with lead alloy: First, the copper beam is degreased and activated. It is degreased in a 5% NaOH solution at a temperature of 60°C for 30 minutes, then immediately rinsed with water, and then immersed in a 5% HNO3 solution for activation for 1 minute at a temperature of 40°C, and then rinsed with deionized water; then the treated copper is placed in a tinning solution at 0.5A / dm 2 Electroplating for 8 minutes at a current density of 15°C, the temperature is controlled at 15°C, the tin plating solution formula is: 20g / L stannous sulfate, 150g / L sulfuric acid, 60000.05g / L polyethylene glycol, 1ml / L OP emulsifier, and then immediately washed with deionized water; then the treated copper is placed in an oven with a temperature of 120°C for drying for 5 minutes, and immediately placed in a molten lead-tin-silver-indium rare earth alloy liquid and hot-dip plated at a temperature of 300°C for 1 minute to obtain a copper conductive beam coated with a lead-tin-silver-indium rare earth alloy; finally, the treated copper conductive beam is placed in a die-casting mold, poured with lead alloy liquid, and die-casted to obtain a copper or copper alloy conductive beam coated with a lead alloy; the mass percentage of tin in the lead-tin-silver-indium rare earth alloy liquid is 8%, the mass percentage of silver is 0.01%, the mass percentage of indium is 0.05%, and the mass percentage of rare earth is 0.005%; the mass percentage of tin in the lead-calcium-tin alloy liquid is 0.1%, and the mass percentage of calcium is 0.03%;

[0143] (2) Preparation of copper rod lead alloy / active cobalt-rare earth / silicon carbide composite anode rod: First, the copper rod was degreased and activated in a 5% NaOH solution at 60°C for 30 min, then immediately rinsed with water, and then immersed in 5% HNO3 for activation for 1 min at 40°C, and then rinsed with deionized water;

[0144] (3) placing the copper rod substrate treated in step (2) in a chemical tin plating solution and soaking it for 30 minutes, controlling the temperature to 50°C, wherein the formula of the tin plating solution is: 10 g / L stannous chloride, 80 g / L trisodium citrate, 10 g / L sodium acetate, 60 g / L thiourea, 60 g / L sodium hypophosphite, pH 0.5, 0.1 g / L ascorbic acid, washing with deionized water and drying with hot air at 100°C;

[0145] (4) Plating the copper rod treated in step (3) in a molten lead-tin-silver-indium rare earth solution at a controlled temperature of 300° C. for 0.1 min to obtain a copper rod lead-tin-silver-indium rare earth alloy; the mass percentage of tin in the lead-tin-silver-indium rare earth alloy solution is 8%, the mass percentage of silver is 0.01%, the mass percentage of indium is 0.05%, and the mass percentage of rare earth is 0.005%;

[0146] (5) placing the copper rod lead-tin-silver-indium rare earth alloy obtained in step (4) in a drawing and extrusion machine at a speed of 16 m / min, controlling the temperature of the drawing die at 80° C., coating the molten lead-calcium-zirconium alloy on the surface of the copper rod lead-tin-silver-indium rare earth alloy by drawing and extrusion, and then cooling the obtained copper rod lead-calcium-zirconium alloy to 0° C. by an ice water freezer, and shearing it into a plurality of copper-based lead alloy rods of the same size as required; the mass fraction of calcium in the lead-calcium-zirconium alloy is 0.06%, and the mass fraction of zirconium is 0.01%;

[0147] (6) The copper-based lead alloy rod obtained in step (5) is cleaned with an acetic acid and hydrogen peroxide solution with a volume ratio of 3:1 and then washed with deionized water, and a layer of active cobalt-rare earth / silicon carbide composite particles is sprayed on its outer surface by explosion spraying to obtain a copper rod lead alloy / active cobalt-rare earth / silicon carbide anode composite rod.

[0148] (7) Preparation of fence-type composite anode plates: First, assemble the anode composite rods obtained in step (6), fix the composite rods constituting the fence-type anode plate support to each other with lead and lead alloy, and fix the left and right sides of the fence-type anode plate support with insulating sheaths, then weld the copper alloy conductive beam to the copper rod of the fence-type anode plate below, then weld the lead alloy layer on the conductive beam to the lead-zirconium alloy layer on the copper rod, and finally install insulators on the plate surface to obtain a fence-type composite anode plate.

[0149] The above-mentioned active cobalt-rare earth / silicon carbide composite particles are prepared by ultrasonic chemical plating. The specific process is as follows: (1) coarsening, sensitization and activation: first, the silicon carbide particles are placed in a mixed solution of 15g / L NH4F+5ml HCl and ultrasonically dispersed at 40°C for 30 minutes, rinsed with deionized water, and then sensitized in a mixed solution of 5g / L SnC12·2H2O+20ml / L concentrated hydrochloric acid at 25°C for 20 minutes, washed with hot water, and then activated in a mixed solution of 1g / L AgNO3+5g / L glucose+10ml ammonia water at 25°C for 30 minutes, and washed with deionized water at 60°C; (2) the activated silicon carbide particles are immersed in a chemical composite plating solution, and a mechanical stirrer and ultrasonic stirring are used during the reaction process. The temperature is controlled at 40°C and the time is 1h. The solution formula is: 20g / L cobalt sulfate, 40g / L trisodium citrate, 3g / L boric acid, 30g / L sodium hypophosphite, 5g / L nano rare earth, pH 8. Polyvinyl pyrrolidone (PVP) 0.1 g / L, washed with deionized water and dried at 110° C. for 1 h to obtain active cobalt-rare earth / silicon carbide composite particles.

[0150] The fence-type composite anode plate for copper electrowinning prepared in this embodiment is electrolyzed in a copper electrolyte under the following conditions: electrolyte copper ion concentration is 50 g / L, sulfuric acid concentration is 180 g / L, electrolyte temperature is 40°C, iron ion is 1 g / L, Cl- ion is 20 mg / L, current density is 300 A / m 2 Compared with the traditional Pb-0.06wt.%Ca-1.2wt.%Sn anode, the fence-type composite anode plate has a 3% higher electrical efficiency, a 140mV lower cell voltage, and a 1.8-fold longer life.

[0151] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0152] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A composite anode plate for copper electrowinning, comprising a conductive beam, a fence-type anode plate support, a lead or lead alloy fixing frame, and an insulating sheath; The surface of the conductive beam is provided with a first lead alloy layer; the conductive beam is composed of a copper rod or a copper alloy rod; The fence-type anode plate support is vertically connected to the conductive beam; the fence-type anode plate support is composed of a plurality of parallel anode composite rods; the anode composite rod is composed of a copper rod or a copper alloy rod, a second lead alloy layer arranged on the surface of the copper rod or the copper alloy rod, and a cobalt-rare earth / silicon carbide particle layer arranged on the surface of the second lead alloy layer; The lead or lead alloy fixing frame is vertically connected to the fence-type anode plate support to fix the anode composite rod of the fence-type anode plate support; The insulating sheath is arranged parallel to the edge side of the fence type anode plate support to fix the edge of the fence type anode plate support; The second lead alloy layer includes a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead-zirconium alloy layer which are stacked in sequence, the tin layer is close to the surface end of the copper rod or copper alloy rod; the lead-zirconium alloy in the lead-zirconium alloy layer is selected from one of lead-calcium-zirconium, lead-calcium-strontium-zirconium, lead-calcium-tin-zirconium, lead-tin-zirconium rare earth, lead-calcium-tin-zirconium rare earth and lead-silver-tin-zirconium rare earth.

2. The composite anode plate for copper electrowinning according to claim 1, characterized in that: The first lead alloy layer includes a tin layer, a lead-tin-silver-indium rare earth alloy layer and a lead alloy layer which are stacked in sequence, the tin layer is close to the surface end of the copper rod or copper alloy rod; the thickness of the tin layer is 1~5μm, and the thickness of the lead-tin-silver-indium rare earth alloy layer is 10~50μm; the thickness of the tin layer is 1~5μm, and the thickness of the lead-tin-silver-indium rare earth alloy layer is 10~50μm; the thickness of the tin layer is 1~5μm, and the thickness of the lead-tin-silver-indium rare earth alloy layer is 10~50μm; the thickness of the first lead alloy layer is 12~30mm, and the thickness of the second lead alloy layer is 3~24mm.

3. The composite anode plate for copper electrowinning according to claim 2, characterized in that: The mass percentage of zirconium in the lead-zirconium alloy is 0.01-0.5%.

4. The composite anode plate for copper electrowinning according to claim 2, characterized in that: The lead-tin-silver-indium rare earth alloy layer has a tin content of 8-18wt%, a silver content of 0.01-0.3wt%, an indium content of 0.05-0.2wt%, and a rare earth content of 0.005-0.1wt%.

5. The composite anode plate for copper electrowinning according to claim 1, characterized in that: The shape of the silicon carbide particles in the cobalt-rare earth / silicon carbide particle layer is rhombus or spherical, the particle size of the silicon carbide particles is 20-500 μm, and the proportion of the silicon carbide particles on the anode plate is 10-50 g / m 2 The particle size of the rare earth is 10~100nm, and its proportion on the anode plate is 5~30g / m 2 .

6. The composite anode plate for copper electrowinning according to claim 1, characterized in that: The cross-section of the copper rod or copper alloy rod is a heterogeneous circle, a heterogeneous cross, a heterogeneous rectangle or a rectangular rectangle; holes are arranged on the surface of the copper rod, and the shapes of the holes are elliptical, circular, square and heterogeneous, the major diameter of the holes is 1-4 mm, and the center distance between the two holes is 10-30 mm.

7. The composite anode plate for copper electrowinning according to claim 1, characterized in that: The material of the insulating sheath is modified PE, modified PP, modified PE-PP, modified PVC-PP or modified PP-ABS; the material of the lead alloy fixing frame is selected from one of lead calcium silver, lead calcium silver strontium rare earth, lead calcium tin rare earth, lead calcium silver tin rare earth and lead calcium silver tin strontium rare earth.

8. The method for preparing the composite anode plate for copper electrowinning according to any one of claims 1 to 7, comprising the following steps: A) cleaning and activating the copper rod or copper alloy rod in sequence, and coating the surface of the activated copper rod or copper alloy rod with a first lead alloy layer; The copper rod or copper alloy rod is sequentially cleaned and activated, a second lead alloy layer is coated on the surface of the activated copper rod or copper alloy rod, and an active cobalt-rare earth / silicon carbide composite particle layer is sprayed on the surface of the second lead alloy layer to obtain an anode composite rod; B) assembling a plurality of anode composite rods into a fence type to obtain a fence type anode plate support; The anode composite rods of the fence-type anode plate support are fixed by lead or lead alloy, and the edge side of the fence-type anode plate support is fixed by an insulating sheath; C) connecting the conductive beam obtained in step A) with the integral fence-type anode plate support obtained in step B) to obtain a composite anode plate for copper electrowinning.

9. The preparation method according to claim 8, characterized in that: In step A), the preparation process of the first lead alloy layer is specifically as follows: Placing the activated copper rod or copper alloy rod in a tinning solution for electroplating and cleaning; the tinning solution comprises: 20-50 g / L stannous sulfate, 150-300 g / L sulfuric acid, 0.05-2 g / L polyethylene glycol, and 1-5 ml / L surfactant; The cleaned copper rod or copper alloy rod is dried and then placed in a molten lead-tin-silver-indium rare earth alloy liquid for hot dip plating, and finally the obtained copper rod or copper alloy rod is placed in a die-casting mold, poured with lead alloy liquid and die-casted; In step A), the preparation of the second lead alloy layer is specifically as follows: Placing the activated copper rod or copper alloy rod in a tin plating solution for chemical plating, wherein the chemical plating tin plating solution comprises: 10-50 g / L stannous chloride, 80-120 g / L trisodium citrate, 10-30 g / L sodium acetate, 60-120 g / L thiourea, 60-120 g / L sodium hypophosphite, and 0.1-0.5 g / L ascorbic acid; Placing the chemically plated copper rod or copper alloy rod in a molten lead-tin-silver-indium rare earth solution for hot-dip plating; The hot-dip-plated copper rod or copper alloy rod is placed in a drawing and extrusion machine to coat the molten lead alloy by drawing and extrusion, and then cooled; The temperature of the drawing and extrusion is 80-300° C., and the speed is 1-16 m / min.

10. The preparation method according to claim 8 or 9, characterized in that: The cobalt-rare earth / silicon carbide composite particles in the cobalt-rare earth / silicon carbide composite particle layer are prepared by ultrasonic chemical plating, specifically: The silicon carbide particles are ultrasonically dispersed in a mixed solution of ammonium fluoride and hydrochloric acid, and then washed with water; then sensitized in a mixed solution of tin chloride dihydrate and concentrated hydrochloric acid, and then washed with water; then activated in a mixed solution of silver nitrate, glucose and ammonia water, and then washed with water; The ratio of the silicon carbide particles to the hydrochloric acid is 1 g: (5-20) ml, and the amount of ammonium fluoride in the mixed solution of ammonium fluoride and the hydrochloric acid is 5-15 g / L; The ratio of the silicon carbide particles to the concentrated hydrochloric acid is 1 g: (10-30) ml, and the amount of the tin chloride dihydrate in the mixed solution of the tin chloride dihydrate and the concentrated hydrochloric acid is 3-15 g / L; The ratio of the silicon carbide particles to the ammonia water is 1 g: (5-20) ml, the amount of the silver nitrate in the mixed solution of silver nitrate, glucose and ammonia water is 1-5 g / L, and the amount of the glucose is 5-10 g / L; The activated silicon carbide particles are subjected to chemical plating, wherein the formula of the chemical plating is: 20-40 g / L of cobalt sulfate, 40-80 g / L of trisodium citrate, 3-10 g / L of boric acid, 30-60 g / L of sodium hypophosphite, 5-20 g / L of nano rare earth, 0.1-0.5 g / L of nonionic surfactant, pH 8-10, washed with deionized water and then dried to obtain active cobalt-rare earth / silicon carbide composite particles.

Citation Information

Patent Citations

  • Composite anode plate for copper electrodeposition

    CN211394653U